Pragmatisme politik kaum elit - Nashir, Haedar. (Pustaka Pelajar, 1999)
Pragmatic political leadership in Indonesia of the elite in power; collection of articles.
Includes bibliographical references (p. 193-196).
Pragmatic political leadership in Indonesia of the elite in power; collection of articles.
Keywords: Political leadership / Indonesia. / http://id.loc.gov/authorities/subjects/sh2010107085; Indonesia / Politics and government / 1966-1998 / http://id.loc.gov/authorities/subjects/sh85065763